Utilization of glucose recovered by phase separation system from acid-hydrolysed oil palm empty fruit bunch for bioethanol production - Mohd Zainudin, Mohd Huzairi; Abdul Rahman, Nor'aini; Abd. Aziz, Suraini; Funaoka, Masamitsu; Shinano, Takanori; Shirai, Yoshihito; Wakisaka, Minato; Hassan, Mohd Ali (Universiti Putra Malaysia Press, 2012)
Oil palm empty fruit bunch (OPEFB) is one the most abundant lignocellulosic wastes produced throughoutthe year in the palm oil industry. A new process of separating lignocellulose components after acid hydrolysis(known as phase separation system) has been previously developed, by which lignin and carbohydrate can becompletely and rapidly separated in 60 minutes between 25 and 30Â°C. In this process, cellulose is completelyhydrolyzed to oligosaccharides and remains in the acid phase. The maximum glucose yield of 53.8% wasobtained by hydrolysis, with 4% acid after autoclaving at 121Â°C for 5 minutes. This work focused on theseparation of monosaccharide (glucose) from cellulose fraction, which was subsequently used as a substratefor ethanol production. For this purpose, different types of nitrogen sources were evaluated, with yeast extractas the best nitrogen source (93% of theoretical yield) as compared to palm oil mill effluent (POME) andsludge powder for the growth of acid tolerant Saccharomyces cerevisiae ATCC 26602. Batch and repeatedbatch fermentation of S. cerevisiae ATCC 26602 using OPEFB hydrolysate gave 0.46 g glucose g ethanol-1,representing 87% of theoretical yield with a productivity of about 0.82 g-1 l-1 h-1 and 0.48 g glucose g ethanol-1,representing 89% of theoretical yield with productivity of about 2.79 g-1 l-1 h-1, respectively.